IDENTITAS KORPORAT DAN PENGARUHNYA TERHADAP DAYA TAHAN STUDI MELALUI REPUTASI DAN KEPUASAN MAHASISWA ANGKATAN 2015 INSTITUT BISNIS DAN INFORMATIKA KWIK KIAN GIE - Imam Nuraryo (Jurnal Ekonomi Perusahaan, 2015)
This research purposes to explain the influence of corporate identity through corporate reputation on student retention and students satisfaction in A business school in jakarta. This research used mixed method, combined with quantitative research method and concurrent embedded strategy model qualitative research method. The theories used in this research are S-O- R theory as middle theory and Information Integration theory and Behavioral Change as applied theory. The results of research indicated that corporate identity simultaneously has influence to the student retention. The influence percentage was 11,9% (small). The corporate identity has very significant influence to the corporate reputation (67,4%). The corporate identity has influence to the student satisfaction. The influence percentage was 12,4% (small). The corporate reputation has significant influence to the student satisfaction (62,1%). The corporate reputation has influence to the student retention. The influence percentage was 14.8% (small). The student satisfaction has influence to the student retention. The influence percentage was 19.3% (moderate).